Caracterisation Physico-Chimique Des Eaux Du Barrage Foum El-Khanga (Region De Souk-Ahras, Algerie) - Allalgua, Amel; Kaouachi, Nouha; Boualeg, Chahinez; Ayari, Adel; Bensouileh, Mourad (European Scientific Journal, ESJ, 2017)
The objective of our work is to assess the quality of the dam Foum El-Khanga (east of Algéria) monthly during the year 2014. This study planned to make a physico-chemical characterization to highlight several parameters which come into play the determination of the quality of this water such as: temperature; pH; conductivity; turbidity; dissolved oxygen; title hydrotimetric; calcium; magnesium; title alcalimetric complet; nitrate; nitrite; ammoniacal nitrogen; sulfate; chloride; bicarbonate; phosphate; iron; biological oxygen demand (BOD) and chemical oxygen demands (COD). The results of physico-chemical analysis show that the water of this dam is characterized by a significant mineralization as indicated by high values of electrical conductivity and chloride. The results of principal component analysis (PCA) clearly showed a stronger relation between the hot season and temperature. However, the cold season was strongly correlated with mineralization and pollution parameters.